Hubungan Intensitas Penggunaan Media Sosial dengan Sindrom FoMO (Fear of Missing Out) pada Remaja - Rasmita, Dina; Zahara, Mutia Unvi; Ariadni, Dwi Karina (Lembaga Penelitian dan Pengabdian Masyarakat Politeknik Muhammadiyah Makassar, 2024)
Social media has developed rapidly over time. Many people today use social media in their daily lives, especially teenagers. FoMO (Fear of Missing Out) syndrome is closely related to a sense of anxiety that occurs due to fear of missing a moment or trend that is spread on the internet or trends that spread on the internet. This is closely related to adolescents who are at high risk of FoMO syndrome. The objective of this research is to determine the connection between teenage FoMO syndrome and the level of social media use. The method used a literature review using articles from the last ten years and has a quantitative design with a correlative approach. The results of this study obtained eight articles. All eight articles found a significant relationship between the intensity of social media use and FoMO syndrome in adolescents. The high use of social media in adolescents causes a teenager to be at high risk of having FoMO syndrome. Excessive use of social media causes adolescents to feel anxious and will cause dependence on social media. Adolescents can use their social media within safe limits to avoid the risk of FoMO syndrome.